2003
DOI: 10.1042/cs20020179
|View full text |Cite
|
Sign up to set email alerts
|

Short-term aerobic training and circulatory function in women: age and hormone-replacement therapy

Abstract: The physiological basis of training responses in women, and particularly older women, is not well understood. Short-term aerobic training (STAT) was used to probe the effects of age and hormone-replacement therapy (HRT) on women's ability to rapidly change peak uptake ( VO(2max)), plasma volume and cardiac function. A total of 39 females participated in the STAT programme: 15 younger (Y; aged 19-29 years), 12 postmenopausal women undergoing HRT and 12 non-medicating postmenopausal (PM) women (aged 60-75 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
3
0
1
Order By: Relevance
“…Although this comparison is not always found in the literature, our results are consistent with those from studies of long-term HRT users (Green et al 1998;Katyal et al 2003;Lee et al 1997;Snabes et al 1996) and 2 short-term crossover studies (Katyal et al 2003;Lee et al 1997). One study reported a higher resting stroke volume (Pines et al 1991) and one a higherpeak exercise cardiac output in women taking HRT (Green et al 1998).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although this comparison is not always found in the literature, our results are consistent with those from studies of long-term HRT users (Green et al 1998;Katyal et al 2003;Lee et al 1997;Snabes et al 1996) and 2 short-term crossover studies (Katyal et al 2003;Lee et al 1997). One study reported a higher resting stroke volume (Pines et al 1991) and one a higherpeak exercise cardiac output in women taking HRT (Green et al 1998).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the average duration of HRT use was 9.4 ± 5.3 years. There appears to be no difference in _ V O 2 max between non-HRT users and short- (Kirwan et al 2004;Snabes et al 1996) and long-term HRT users (Green et al 1998;Johnson et al 2002;Katyal et al 2003;McCole et al 2000;Moreau et al 2002Moreau et al , 2003. Erickson et al (2007) reported no difference in _ V O 2 peak between short-, mid-, and long-term HRT users.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The few studies performed to date (24)(25)(26) have focused on aerobic based exercise interventions. Overall, the findings of these studies suggest that the increase in VO 2peak associated with AT is due to the improvement in peak arteriovenous oxygen difference, as no significant change was found for heart rate (24,25), end diastolic volume (24), end systolic volume (24), stroke volume (24,25), ejection fraction (24,26), or cardiac output during peak exercise (24,25). Failure of older women to increase their stroke volume after AT has been linked to the inability of the senescent female heart to develop eccentric hypertrophy (27).…”
Section: Discussionmentioning
confidence: 99%
“…O fato da terapia estrogênica não ter influenciado as respostas de capacidade aeróbia máxima (VO 2máx ), confome verificado em estudos prévios 65,66 .…”
Section: Discussionunclassified